Conventional pap’s test and liquid-based cytology for the screening of cervical cancer with back up colposcopy directed biopsy (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The aim of this study was to screen the suspected cervical cancer patients (n=100) by liquid-based cytology and conventional pap’s smear followed by colposcopic biopsy from July 2016 to June 2017. In conventional pap’s test, 73 cases were true negative whereas 25 cases were false negative. However, in liquid-based cytology, 68 cases were true negative and 23 cases were false negative. Finally when colposcopic examinations were done, 61 cases were true negative and 15 cases were false negative. The sensitivity of liquid-based cytology was 11.5% for cervical cancer screening which was more than the conventional pap’s smear (3.8%). In conclusion, liquid-based cytology should be more preferable method than the than conventional pap’s smear for the diagnosis of precancerous lesion of the cervix.